Studi Literature: Pengaruh Culture Terhadap Kreativitas Kinerja Karyawan - Regi Cahyadi Saputra; Dety Mulyanti (Lembaga Pengembangan Kinerja Dosen, 2023)
Corporate culture or corporate culture are the values ​​that are adopted, implemented, and maintained within a company. An organization with a strong culture will influence the behavior and effectiveness of employee performance. The purpose of this theoretical review is to find out how culture influences employee performance creativity. The method used is a theoretical review by analyzing and comparing existing theories. The result of this theoretical review is that the influence of culture on the creativity of employee performance has a significant and large effect. There is a positive and significant influence between creativity and employee performance, meaning that high or low creativity will affect high or low employee performance. It can be concluded that culture serves as the social glue that helps hold the company together by providing proper standards for what employees should say and do. Culture can also affect the creativity and performance of employees. For companies it is important to improve performance and build employee culture and creativity through achieving the implementation of an activity or policy in realizing the goals, objectives, vision and mission of the organization as outlined through the strategic planning of an organization or company.